2016
DOI: 10.3758/s13428-016-0765-6
|View full text |Cite
|
Sign up to set email alerts
|

SubsMatch 2.0: Scanpath comparison and classification based on subsequence frequencies

Abstract: Our eye movements are driven by a continuous trade-off between the need for detailed examination of objects of interest and the necessity to keep an overview of our surrounding. In consequence, behavioral patterns that are characteristic for our actions and their planning are typically manifested in the way we move our eyes to interact with our environment. Identifying such patterns from individual eye movement measurements is however highly challenging. In this work, we tackle the challenge of quantifying the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 52 publications
(52 reference statements)
1
37
0
Order By: Relevance
“…R-Rl is the transition from total rainy days to rainy days with low pressure). An analysis of longer subsequences was not performed as the possible number of unique transition patterns increases dramatically with the pattern length, and each tends to occur with a much lower frequency, leading to sparse data that is difficult to interpret (Kübler et al 2017;. To identify significant differences in the distribution of transitions between the Correct and Incorrect groups, two permutation tests, one for each condition, with 10,000 permutations each were performed using the Hellinger distance as defined by equation 2.…”
Section: Discussionmentioning
confidence: 99%
“…R-Rl is the transition from total rainy days to rainy days with low pressure). An analysis of longer subsequences was not performed as the possible number of unique transition patterns increases dramatically with the pattern length, and each tends to occur with a much lower frequency, leading to sparse data that is difficult to interpret (Kübler et al 2017;. To identify significant differences in the distribution of transitions between the Correct and Incorrect groups, two permutation tests, one for each condition, with 10,000 permutations each were performed using the Hellinger distance as defined by equation 2.…”
Section: Discussionmentioning
confidence: 99%
“…Plotting a receiver operating characteristic curve, the authors reported a 76% sensitivity at 90% specificity. Kübler, Rothe, Schiefer, Rosenstiel, and Kasneci (2017) obtained above-chance-level results when separating patients (glaucoma and hemianopia) who failed at a driving task from patients who succeeded at the same task, as well as a healthy control group.…”
Section: Inference From Gaze Datamentioning
confidence: 93%
“…Previous research (Nodine et al 1993) has indicated that feature importance is correlated with a variety of gaze response data variables such as fixation time (Isham and Geng 2013), fixation points, and first-located time (Kubler et al 2017). This gaze data provided insight into how people evaluate the features while making preference decisions (Du and Macdonald 2014, Ho and Lu 2014, Husic-Mehmedovic et al 2017).…”
Section: Effect Of Tang Dynasty Chair Features On Eye Movements In Kamentioning
confidence: 99%